Psychometric testing of a short-form questionnaire for the measurement of health experiences among people with musculoskeletal disorders undergoing multimodal rehabilitation - Birgitta Wiitavaara; Dag Rissén; Hans Högberg; Annika Nilsson (BMJ Open)
Aim The aim of the present study was to assess if a previously suggested short-form questionnaire tested among women with non-specific neck-shoulder pain is suitable also for use among men and women with non-specific musculoskeletal disorders in any part of the body, by testing its construct validity by a confirmatory factor analysis. If not, the secondary aim was to investigate the evolving factor structure when performing an explorative factor analysis of data in the expanded sample.Methods Questionnaire data were collected in three different contexts, in primary care via eight different multimodal rehabilitation teams and in specialised care via two different specialist care centres. The sample consisted of 116 men (n=29) and women (n=87) with non-specific musculoskeletal disorders.Data were analysed using confirmatory and exploratory factor analysis and a visual comparison between the result of the principal component analysis in the present study and the results attained in a previous study with a similar aim and design.Results The confirmatory factor analyses did not end up in a model with acceptable measures for validity. Three models were tested, none of them met the criterion for an acceptable model, and the goodness-of-fit statistics were not fully acceptable. The exploratory factor analysis had only partly comparable result compared with previous study.Conclusion The results of the present study did not prove the suggested short-form questionnaire to be suitable for evaluation of symptoms among men and women with non-specific musculoskeletal disorders in any part of the body. Further studies including larger samples are recommended.Trial registration number 92199001.